VD_FINDINFO Décision / 2014 / 55 vom 10. Februar 2014 - VD Tribunal cantonal (2014)
DÉFENSE NÉCESSAIRE, AUDITION OU INTERROGATOIRE, ACTE ILLICITE | 130 let. b CPP (CH), 131 CPP (CH), 132 CPP (CH), 141 al. 5 CPP (CH)